Dampak Covid-19 Pada Kinerja Saham Sektor Perdagangan, Jasa & Investasi Dan Aneka Industri - Novianti, Neva; Herawati, Herawati; Putri, Tyara Dwi; Zaitul, Zaitul (E-Jurnal Akuntansi, 2022)
The COVID-19 pandemic has hit almost all countries in the world, including Indonesia. For this reason, Indonesia has implemented PSBB measures to overcome the spread of the virus. This study intends to explore the impact of Covid-19 on stock returns in the trade, services & investment sectors and various industries and see the relationship between these sectors. The data used are financial report data, stock prices and the number of confirmed cases of Covid 19 with an observation period of 14 days before the PSBB was implemented, namely from 27 March 2020 and 14 during PSBB. The total sample is 163 companies. This research methodology adopts a panel data regression approach. Research shows that the increase in the number of confirmed cases of Covid-19 has no effect on stock returns. However, during the PSBB period, the trade, services and investment sectors showed a significant positive effect on stock performance. In addition, the two sectors studied also showed different results. Keywords: Covid-19; PSBB; Stock Returns.